Genetic study of weight at different ages in exotic, desi and their haltbred pigs - PANDEY, R N; SINGH, S K; SINGH, R L; DUBEY, C B (The Indian Journal of Animal Sciences, 2013)
Six genetic groups of pig consisting of 792 progenies were studied. Genetic group and weaning weight had highly significant effect on body weight at all the ages whereas. sex and interaction between genetic group x sex had nonsignificant influence at all the ages except at 12th and 16th weeks for interaction. Birth weight had highly signiticant influence during preweaning period but its effect was nonsignificant during postweaning period. The effect of season of birth was signiticant during most of the postweaning periods whereas, nonsignificant during preweaning periods except birth weight. Litter size at birth had significant effect on preweaning body weight at all the ages except at birth. In general, higher body weight was observed in Hampshire than those of Large White and T and D followed by haltbreds (LWY x D and H x D) and desi. Almost similar growth rate was recorded in T and D and L WY haltbreds but both were significantly superior to Hampshire haltbreds. During preweaning period, body weight was negatively correlated with litter size at birth of their dam. whereas weaning weight was positively correlated with postweaning growth rate. The genetic correlations among successive ages were very high and that even the phenotypic correlation were relatively high and increased with age. It is possible therefore to select for large body size relatively early in life.